Konsep Keselamatan dalam Teologi Kristen Modern - Juara Juara (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Safety is the main goal of life in this world and in the hereafter. Safety means being safe. Salvation in theology is referred to as the main point of the Christian faith as human divinity as mercy and forgiveness of sins. Religion in general gives instructions to its people through the holy book which is one of the main foundations as a guide for life. The aim is for adherents of religion to receive safety, both in this world and in the hereafter, physically and spiritually. To achieve salvation in Christianity through faith, baptism, repentance, turning, rebirth and forgiveness. The development of the teachings of salvation in Christianity has occurred since the Second Vatican Council (1962-1965) where a reform occurred in the Catholic and Protestant churches which resulted in a renewal. Church renewal of religious teachings according to Luther and Calvin. According to Luther, the forgiveness of sins because of the blood of Jesus is a gift from God. According to Calvin, he prioritized the majesty of God and the power of God without any ties. Based on the results of this study, the authors can understand the concept of the salvation of modern Christianity, will make themselves more appreciative and respectful of other religions. Abstrak Keselamatan merupakan tujuan utama hidup di dunia dan di akhirat. Keselamatan artinya keadaan selamat. Keselamatan dalam teologi disebut dengan pokok iman Kristen sebagai pengilahian manusia sebagai rahmat dan pengampunan dosa. Agama pada umumnya memberikan petunjuk pada umatnya melalui kitab suci yang merupakan satu landasan utama sebagai penuntun hidup. Tujuannya adalah agar umat pemeluk agama mendapat keselamatan, baik di dunia maupun di akhirat, jasmani maupun rohani. Untuk mencapai keselamatan dalam agama Kristen melalui keimanan, pembaptisan, pertobatan, perpalingan, kelahiran kembali dan pengampunan. Perkembangan ajaran keselamatan dalam agama Kristen terjadi sejak Konsili Vatikan II (1962-1965) terjadi suatu reformasi dalam gereja Katolik maupun Protestan yang lahir suatu pembaharuan. Pembaharuan gereja terhadap ajaran agama menurut Luther dan Calvin. Menurut Luther, pengampunan dosa karena darah Yesus adalah anugerah Allah. Menurut Calvin, ia lebih mengutamakan keagungan Allah dan kuasa Allah tanpa ikatan apa pun. Berdasarkan hasil penelitian ini penulis dapat memahami konsep keselamatan agama Kristen modern, akan menjadikan diri semakin menghargai dan menghormati agama lain.